Enhancing Mandarin Teaching in Indonesia through a Cross-Cultural Awareness: A Comprehensive Training Program for Chinese Mandarin Teachers - Yulianto, Bambang; Sueb, Sueb; Harmanto; Trisusana, Anis; Asteria, Prima Vidya; Subekti, Hasan; Hidayah, Layli; Murniatie, Itznaniyah Umie (International Journal of Research and Community Empowerment, 2024)
This article exposes the implementation and effectiveness of a cross-cultural training program designed for Mandarin teachers from China who instruct students in Indonesia. The training aims to equip these Mandarin teachers with a deeper understanding of the Indonesian context, fostering cultural sensitivity and diversity to enhance their teaching approaches in Indonesia. The study describes the impact of this cross-cultural approach on the teachers based on their perception in terms of the effectiveness in promoting a more inclusive and effective Mandarin language education in the Indonesian setting. The study involved 13 Mandarin teachers from China who teach Mandarin in Surabaya. The results show positive feedback from the Mandarin teachers upon the inclusive Mandarin education through cross-cultural approach and it is effective for future teaching planning. This study highlights the importance of the cross-cultural understanding for second language learning. It can be accommodated by either training or courses provided at the campus for teacher candidates of foreign language.